Reduced CBF recovery detected by longitudinal 3D‐SSP SPECT analyses predicts outcome of postoperative patients after subarachnoid haemorrhage. (28th November 2017) - Mutoh, Tatsushi; Totsune, Tomoko; Takenaka, Shunsuke; Tatewaki, Yasuko; Nakagawa, Manabu; Suarez, Jose I; Taki, Yasuyuki; Ishikawa, Tatsuya
Summary: The aim of this study was to evaluate the impact of cerebral blood flow (CBF) recovery obtained from brain single‐photon emission computed tomography (SPECT) images on postoperative outcome after aneurysmal subarachnoid haemorrhage (SAH). Twenty‐nine patients who had undergone surgical clipping for ruptured anterior communicating artery aneurysms were analyzed prospectively. Routine measurements of CBF were performed using technetium‐99 m hexamethyl propyleneamine oxine SPECT on days 4 and 14 after SAH. Regional voxel data analyzed by three dimensional stereotactic surface projection (3D‐SSP) were compared between patients and age‐matched normal database (NDB). In 3D‐SSP analysis of all patients, cortical hypoperfusion around the surgical site in bilateral frontal lobes was evident on day 4 ( P  < .05 vs NDB), which was improved significantly on day 14. However, the recovery was less complete in patients with poor clinical grades ( P  < .05) and presenting symptoms attributable to delayed cerebral ischaemia (DCI) ( P  < .05) than those without. Multivariate analysis showed that patients with mild to moderate CBF recovery (relative Z‐score differences of <4) ( P  = .014; odds ratio, 2.5; 95% confidence interval, 1.93–3.31) was independently associated with poor functional outcome at 3 months. We conclude that reduced CBF recovery detected by serial 3D‐SSP SPECT image analyses can be a potential predictor of poor prognosis in postoperative patients after SAH.